The Development of Indonesian Vocabulary in the Digital Era: A Literature Review on Neologisms and Linguistic Adaptation in Information Technology - , Elistyani; I Made Juliarta; Komang Astiari (Focus Journal : Language Review, 2025)
This literature review examines the development of Indonesian vocabulary in the digital era, focusing on neologisms and linguistic adaptation within information technology contexts. The study employs a qualitative literature review methodology, analyzing scholarly publications from 2020 to 2025 to understand patterns of vocabulary development, sociolinguistic factors, and integration processes in contemporary Indonesian usage. The analysis reveals five distinctneologism formation patterns: direct borrowing from English, hybrid formation combining foreign elements with Indonesian morphological structures, extensive use of acronyms and abbreviations, morphological creativity through affixation processes, and semantic extension of existing Indonesian words to accommodate digital meanings. Sociolinguistic factors significantly influencing vocabulary adaptation include generational differences, educationalbackground, urban-rural divides, social media platform preferences, professional domain requirements, and regional linguistic variations. Integration levels vary considerably across different contexts, with terms like "internet" and "computer" achieving high integration in formal settings, while newer terms remain primarily in informal usage. Comparative analysis demonstrates that Indonesian occupies an intermediate position in global digital vocabularyadaptation, showing more flexibility than languages with strong resistance policies but maintaining creative adaptation mechanisms that preserve linguistic identity. The study identifies significant implications for language policy and planning, highlighting tensions between prescriptive terminology development and descriptive usage realities. The research reveals substantial gaps in longitudinal studies, corpus linguistics applications, and psycholinguistic investigations of digital vocabulary processing. The findings contribute to understanding how local languages adapt to global technological advancement while maintaining cultural and linguistic identity in digital environments.